The Development of a Novel Interdisciplinary Chronic Pelvic Pain Program - Laura Katz; Adria Fransson; Ramesh Zacharias (Taylor & Francis Group, 2019)
Introduction: Chronic pelvic pain (CPP) is a significant issue for women, with approximately 14% of women experiencing CPP at least once in their life. CPP is chronic and debilitating associated with significant costs and morbidity, and its etiology is multifactorial often complicating medical treatment and symptom management. Best practice guidelines recommend an interdisciplinary and biopsychosocial approach to treatment. The aim of this poster is to describe the ongoing development and evaluation of a novel Interdisciplinary CPP Program at the Michael G. DeGroote Pain Clinic. Methods: Female patients were referred to the Program from community gynecologists and urologists, and were scheduled for an orientation to learn about the Program. Patients were then scheduled for an interdisciplinary assessment (psychology, physiotherapy, internal pelvic examination), and if appropriate were scheduled for the Program. The Program occurs once a week for 8 weeks, and each day consists of physiotherapy, psycho-education, goal setting, and mindfulness. Preliminary Results & Discussion: Ninety-four referrals have been received since January 2018. Eight out of nine patients completed the first Program, and assessments and programs are ongoing. In terms of the demographics of the first sample of patients, the mean age was 33.3 ± 6.2, they last worked 2.8 ± 2.2 years ago, their pain started 10.1 ± 7.5 years ago, with predominantly an underlying diagnosis of endometriosis (77.8%). Ninety percent reported a history of anxiety/panic and depression. Upon discharge, all outcomes measures showed improvements. As the Program develops, future research will evaluate the statistical changes in outcomes, and will continue to support women coping with CPP.